The Impact of Remote Work on Employee Engagement and Well-being: A Comparative Analysis Before and After the COVID-19 Pandemic (Trinity Journal of Management, IT & Media (TJMITM), 2025)
Remote work, once considered a niche practice, has become a mainstream phenomenon in response to the COVID-19 pandemic. Organizations worldwide have swiftly transitioned to remote work arrangements to ensure business continuity and employee safety. While remote work offers benefits such as flexibility and reduced commuting stress, it also poses challenges for maintaining employee engagement and well-being. This paper aims to investigate how remote work has influenced employee engagement and well-being, both before and after the pandemic, using theoretical frameworks to guide the analysis.
Keywords: employee safety; phe nomenon; pandemic; theoretical frameworks